Investigation of reduced susceptibility to glycopeptides among meticillin-resistant Staphylococcus aureus recovered in Ireland (1998-2004) - Fitzgibbon, Margaret (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2009)
Meticillin-resistant Staphylococcus aureus (MRSA) isolates (n=3,189) from 2990 patients were studied by agar screening and the E-test™ macromethod to investigate reduced susceptibility to glycopeptides among six collections of MRSA recovered between 1998 and 2004. No vancomycin-resistant S. aureus or glycopeptide-intermediate S. aureus (GISA) were detected but 178 isolates were confirmed by vancomycin population analysis profile (PAP)-area under the curve (vPAP-AUC) ratio determination and/or teicoplanin PAP (tPAP) methods as hetero-GISA (hGISA). Of 139 isolates detected using recommended E-test™ macromethod cut-off values of ≥8 mg/L for both vancomycin and teicoplanin or ≥12 mg/L for teicoplanin alone, 73 were confirmed as hGlSA by vPAP- AUC, 95 by tPAP and 108 by both methods. Lowering the teicoplanin E-test™ macromethod cut-off value to 8 mg/L detected a further 70 hGISA (17 were confirmed by vPAP-AUC and 70 by tPAP).
Keywords: Clinical Microbiology, Ph.D.; Ph.D. Trinity College Dublin